Natural biomolecules and derivatives as anticancer immunomodulatory agents - Bernitsa, Stavroula; Dayan, Rotem; Stephanou, Anastasis; Tzvetanova, Iva D.; Patrikios, Ioannis S. (Frontiers in Immunology, 2023)
Despite the advancement in chemotherapy as the principal treatment for many cancers, there still remains the issue of chemoresistant and non-responsiveness against the many chemotherapeutic drugs that are known. More recent, cancer immunotherapy has become a novel antitumor treatment for selective cancers based on their defective gene mutation. However, further effective strategies to improve immunotherapy efficacy for anticancer treatment is also an emerging area of development. In recent years, the use of natural phytochemicals, known to have anticancer properties, have also been reported to mediate their effects by modulating immunity. Thus, the mechanism of phytochemical mediated-immunomodulatory activity may be attributed to the remodelling of the tumor immunosuppressive microenvironment. In this review, we will discuss several well-known plant-derived biomolecules and examine their potential as immunomodulators and therefore as novel immunotherapies for cancer treatment.